WHITE DUST SIMULATION FOR TAILINGS POND OF ERDENET COPPER MINING USING HYSPLIT - B, Lkhagvajargal; Ch, Sonomdagva; Ch, Byambatseren; B, Batdelger (Proceedings of the Mongolian Academy of Sciences, 2018)
The purpose of this research was to identify dispersion and transporting of white dust for tailings pond of Erdenet copper mining in Mongolia. Spring and autumn have a significantly higher level of PM10 mass concentration in Erdenet city. Probably caused by the stagnant atmosphere which leads to pollution’s cumulative effect and ‘white dust’ from the storage of tailings pond in spring and autumn. We used meteorological data for 2015 gathered from Information and Research Institute of Meteorology, Hydrology and Environment (IRIMHE) in Erdenet city and GDAS meteorological data provided by U.S NOAA. In the present study, white dust simulation by using the ArcGIS, HYSPLIT program modeling. The Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) model is used to identify the white dust dispersion and transportation trends. According to the simulation from model HYSPLIT, white dust was spread between 14 and 65 km in 2015. The main month of white dust distribution was May and October when mass concentration of PM10 was high due to white dust. White dust distribution was four times lower when the rainy day.